A Breif Review of the Effects of Physical Activity in Subjects with Cardiovascular Disease: An Interpretative Key - Gaetano Altavilla; Francesca D'Elia; Gaetano Raiola (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Today is consolidated the importance of physical activity to health, so it is important to know the eff ects of exercise for primary prevention and secondary. A regular physical activity of mild intensity results in signifi cant benefi ts in term of health, while a sedentary lifestyle and otherrisk factors contributeto development of chronic degenerative diseases, in particular cardiovascular. The advanced age does not contraindicate physical activity and exercise can prevent cardiovascular and disability diseases in the elderly. In the elderly person physical exerciseis able toimprove muscular tone and movement skills, of reduce the risk of sudden death caused by cardiovascular diseases, of reduce the development of tumors and metabolic disorders, as well as of delay the decline of cognitive function. The aim of this literature review is to clarify the link and the eff ects between physical activity, aging and cardiovascular diseases, providing practical indications for a useful physical activity for elderly subjects with cardiovascular problems;adapting to the skills of the elderly person, prescribed after careful assessment of the environmental conditions in which it must take place. In conclusion, a physical activity program fi nds a sure indication both in elderly subjects without and with pathologies and in the elderly with high risk of disability